Ceramic surface pattern for walls / Nurul Izza Ab Aziz, Azni Hanim Hamzah and Shahidah Abdul Razak - Ab Aziz, Nurul Izza; Hamzah, Azni Hanim; Abdul Razak, Shahidah (2012)
Malaysia is one of the richest countries with a lot of natural resources among them, clay. Due to this, researcher makes an innovative about ceramic surface pattern design and applies at wall building. It aims at applying and enhancing astonishing environment through walls as a visual art. Apart from that, to increase public awareness and understanding on ceramic is essential. This research has been conducted by using structured questionnaires. It is highly hoped that this research will assist more clearly on the educational, technical and aesthetic validity at the same time increase our competitiveness in this interesting field.